Assessment the Effect of Different Genotypes of Sulfotransferase 1A1 Gene on the Response to Monoxide in Patients with Androgenic Alopecia - Moaed E. Al-Gazally (Journal of Global Pharma Technology, 2017)
Objective is to assess the association between a specific genotype and the response to monoxide in patients with androgenic alopecia. Methods and materials: This study was conducted with the participation of thirty five androgenic alopecia patients. The presence of G<A single nucleotide polymorphism in the sulfotransferase 1A1 gene is detected by restricted fragment length polymorphism polymerase chain reaction technique. Result: In this study, it was found that the levels of response to monoxide are differ with different genotypes of the sulfotransferase 1A1 gene, and there is significant association between the allele type and the response to monoxide. The G allele is significantly associated to the response in a p- value of 0.016 and also there is significant association to the GG genotype in a p- value of 0.0011, while it is insignificant to the GA genotype. Conclusion: The results of this study indicate that the monoxide is effective for those patients who are carrying the GG genotype of the sulfotransferase 1A1 gene, and that can be used as a genetic test to predict the response monoxide.